NbCl5 Promoted the Efficient Synthesis of Phthalein Derivatives: Optical Characterization and Solvatochromic Effect - Moreno, Vitor Fernandes [UNESP]; dos Santos, Giovanny Carvalho [UNESP]; da Costa, Gyordanna Mayara Gaspar [UNESP]; Gomes, Marcelo Henrique Ayala [UNESP]; Silva-Filho, Luiz Carlos da [UNESP] (My University, 2019)
Organic dyes derived from phthaleins have a large number of industrial applications and can be synthesized using a Lewis acid by Friedel–Crafts acylation, followed by an addition reaction to the carbonyl compound. This work aims to investigate the use of NbCl5 as a catalyst for the acylation reaction. The behavior of the phthalein derivatives in several solvents and when subjected to different pH conditions was studied. These compounds showed a color-changing effect depending on the pH and solvent, making them useful for applications as indicators. The phthaleins change their conformations depending on the condition of the medium. Photophysical studies of these compounds were carried out through their UV–Vis absorption spectra. Here, we show the umbrella-like conformation change of phthalein derivatives that depend on the solvent and the pH of the medium.